Revitalisasi Tudung Saji Atau Sange (Studi Kasus: Kabupaten Aceh Jaya) - Alviony Maulida Putri; Bunayyati Hakimah Sembiring Meliala; Dewi Suta Ningsih; Farah Diana Rohim; Ginta Dwiki Meliana; Muhammad Hanif; M. Rosyid Rabbani; Nakiatul Misqa; Rahmad Muhayat Syah; Silvi Rahmadani; Togar; Wahyu Firdaus; Abd. Mujahid Hamdan (Jurnal Riset dan Pengabdian Masyarakat, 2023)
Sange products or decorative serving hoods are a typical cultural heritage of the village of lamtui, Aceh Jaya. The Sange is used for generations by the Lamtui village community. But over time, decorative or sange serving hoods have declined due to so much competitiveness, manual manufacturing and the entry of modern culture, even foreign cultures. This has resulted in many who do not know of the existence of decorative serving hood or Sange which is a characteristic of the gampong or lamtui village. With the declining situation, it is feared that today's young generation will no longer know him. So this research aims are: Efforts to revitalize Sange or Tudung Saji in the manufacturing process, motives and marketing. and This research uses a qualitative approach. Data collected through observation, interviews and documentation. The data obtained in the form of oral and written data and pictures